2014
DOI: 10.1521/jscp.2014.33.5.463
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Disorder Features, Self-Verification, and Committed Relationships

Abstract: This article was originally published in the Journal of Social and Clinical Psychology. The version of record can be found here: http://guilfordjournals.com/doi/abs/10.1521/jscp.2014.33.5.463This study examines whether self-verification strivings are greater for individuals with elevated features of Borderline Personality Disorder (BPD) than individuals with minimal features of BPD, and whether this is especially true for those in committed romantic relationships. Participants (N = 329) completed an online que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…Total scores are calculated by summing items 1 through 10, and Zanarini et al (2003) have suggested a cutoff of seven or greater as screening “positive” for BPD. In the current sample, the MSI‐BPD demonstrated good internal consistency ( α = 0.80), similar to prior studies utilizing college samples (Bracken‐Minor & McDevitt‐Murphy, 2014; Brickman et al, 2014; Valentiner et al, 2014).…”
Section: Methodssupporting
confidence: 84%
“…Total scores are calculated by summing items 1 through 10, and Zanarini et al (2003) have suggested a cutoff of seven or greater as screening “positive” for BPD. In the current sample, the MSI‐BPD demonstrated good internal consistency ( α = 0.80), similar to prior studies utilizing college samples (Bracken‐Minor & McDevitt‐Murphy, 2014; Brickman et al, 2014; Valentiner et al, 2014).…”
Section: Methodssupporting
confidence: 84%
“…On the other hand, individuals with BPD may have emptiness or abandonment feelings, unstable self image, emotional instability and impulsivity. So this situation may reflect as conflict into relationships (Valentiner, Hiraoka & Skowronski, 2014). Sexual rarity was reported during to depression, so sexual problems may be dependent on the changes related with BD (Lam, Donaldson, Brown & Malliaris, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(Cassidy, Aikins, et al, 2003;Finkenauer et al, 2002;Leary, 2007;Rosen et al, 2013;Swann, Rentfrow, et al, 2003 (Cassidy, Aikins, et al, 2003;Cassidy, Ziv, et al, 2003;North & Swann, 2009;Polzer et al, 2002;Rosen et al, 2013;Swann, 2012 . ‫الذات‬ ‫عن‬ ‫السمبية‬ ‫اء‬ ‫اآلر‬ ‫ذوى‬ ‫اد‬ ‫األفر‬ ‫بين‬ ‫االنتباه‬ ‫يمفت‬ ‫وما‬ ‫من‬ ‫التحقق‬ ‫فى‬ ‫الرغبة‬ ‫تفوقيا‬ ‫ما‬ ‫ا‬ ً ‫دائم‬ ‫أنيا‬ ‫إال‬ ‫اإليجابية،‬ ‫فى‬ ‫الرغبة‬ ‫قوة‬ ‫من‬ ‫الرغم‬ ‫عمى‬ ‫أنو‬ ‫ىو‬ ‫الذات‬ (Anseel & Lievens, 2007;Chen et al, 2004;Pettit & Joiner, 2001; Polzer et al, 2002;Swann et al, 2000Swann & Pelham, 2002;Swann, Polzer, et al, 2004;Valentiner et al, 2014;Wiesenfeld et al, 2017) ‫إلى‬ (Botana, 2011;Gómez et al, 2009;Swann, Kwan, et al, 2003; (Ashford et al, 2003;Morrison, 2002;Morrison et al, 2004;Qian et al, 2016 (Ashford & Black, 2006;Anseel & Lievens, 2007;Auh et al, 2019;Wanberg & Kammeyer-Mueller, 2000) ‫ا‬ (Swann & Pelham, 2002) ‫كان‬ ‫إذا‬ ‫حتى‬ ‫االكتئاب‬ ‫شديدة‬ ‫لمذات‬ ‫ات‬ ‫نظر‬ ‫لدييم‬ (Pettit & Joiner, 2001) . ‫و‬ ‫أكدتو‬ ‫ما‬ ‫ىذا‬ ‫اسات‬ ‫الدر‬ ‫من‬ ‫العديد‬ ‫نتائج‬ (Neff & Karney, 2003Rosen et al, 2013;Swann et al, 2000 Ashford Ashford, 2016;…”
Section: Introductionunclassified